(untitled) (ENTHYMEMA, 2011)
Review of Mario Lavagetto, Quel Marcel! Frammenti della biografia di Proust. Torino: Einaudi 2011, a work where some of the biographical elements found in the letters of Marcel Proust are confronted with their transfiguration both in the early works (where at first it appears to be vague, and then more precise and methodical) and then in the Recherce, where these elements appear in a very different way.